Penerapan Intervensi Senam Kaki Diabetik Terhadap Penurunan Kadar Gula Darah Pada Lansia Dm Di Wilayah Kerja Puskesmas Pancoran Mas Kota Depok - Angela Adista Pramesti; Saka Adhijaya Pendit; Teti Oktianingsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
One of the most serious health problems facing the elderly in the world is Diabetes Mellitus. Diabetes mellitus not only causes premature death worldwide, this disease is also a major cause of blindness, heart disease, and heart failure (Ministry of Health of the Republic of Indonesia, 2020). Diabetes mellitus foot exercises are physical exercises that can be done by people with diabetes mellitus. Foot exercises are activities or forms of exercise carried out by people with diabetes mellitus to prevent wounds and improve blood flow in the feet. The aim of this study was to determine the effect of implementing Diabetic Foot Exercise interventions on reducing blood sugar levels in elderly people with DM, in the working area of the Pancoran Mas Health Center, Depok City. The population in this study was 37 elderly people. The sample size was 15 respondents. This study used a quasi-experimental design, with a one-group pre-test post-test approach. Using Paired Sample T-Test. Based on the results of the study, the results obtained with the Paired Sample T-Test obtained a mean of 3.60000, Std. Deviation of 0.96609, and Sig. (P Value) of 0.000 <0.05, concluding that there is an influence between the results of reducing blood sugar levels in the data before and after being given Diabetic Foot Exercise intervention. The results state that the scale of reducing blood sugar levels of respondents before and after being given Diabetic Foot Exercise intervention is effective.